Implant survival after surgical treatment of peri‐implantitis lesions by means of deproteinized bovine bone mineral with 10% collagen: 10‐year results from a prospective study. Issue 8 (24th July 2020) - Roccuzzo, Mario; Fierravanti, Ludovica; Pittoni, Dario; Dalmasso, Paola; Roccuzzo, Andrea
Abstract: Objectives: To evaluate the 10‐year outcomes of a regenerative surgical treatment of single peri‐implantitis intrabony defects, by means of deproteinized bovine bone mineral with 10% collagen (DBBMC). Material and Methods: The original population consisted of 26 patients with one crater‐like defect, around either SLA or TPS dental implants, with a probing depth ≥6 mm and no implant mobility. After debridement and surface decontamination, the defects were filled with DBBMC. Subsequently, patients were placed in an individualized supportive peri‐implant/periodontal therapy (SPT) program. Results: Fourteen patients (eight SLA and six TPS) reached the 10‐year examination. The overall implant survival rate was 67%, 80% for the SLA, and 55% for the TPS implants. During SPT, five patients were lost to follow‐up, eight patients needed additional antibiotic and/or surgical therapy, and seven patients had the implant removed. PD was reduced from 6.6 ± 1.3 to 3.2 ± 0.7 mm in SLA and from 7.2 ± 1.5 to 3.4 ± 0.6 mm in TPS. BOP decreased from 75.0 ± 31.2% to 7.5 ± 12.1% (SLA) and from 90.0 ± 12.9% to 30.0 ± 19.7% (TPS). Treatment success was found in 5 of the 12 SLA (42%) and in 4 of the 14 TPS (29%). Conclusions: The proposed reconstructive treatment, followed by SPT, was able to maintain in function the majority of SLA implants, although the overall treatment success was limited and many of TPS implants were removed. Therefore, the decision to treat implants affected by peri‐implantitis should be based on several factors, including surface characteristics.